2018
DOI: 10.3389/fmars.2018.00149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sample Fixation on Specimen Identification in Biodiversity Assemblies Based on Proteomic Data (MALDI-TOF)

Abstract: Recently, MALDI-TOF mass spectrometry has been used to reliably identify taxonomically difficult harpacticoid copepods from sediment samples. In agreement with former studies, a negative impact of short storage periods was stated. Other studies reported inferior mass spectra quality from samples fixated in varying ethanol concentrations. Therefore, sediment samples from a mudflat sampling site in the North Sea were stored under different temperature conditions to explore possible storage effects. Samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 54 publications
4
35
0
Order By: Relevance
“…30 for calanoid copepods. Successful identification of smaller harpacticoid copepods was already shown by Rossel and Martínez Arbizu 31,32 . Amongst others, the authors emphasized the importance of sediment sample storage at low temperatures for MALDI-TOF MS applications 32 .…”
Section: Introductionmentioning
confidence: 74%
“…30 for calanoid copepods. Successful identification of smaller harpacticoid copepods was already shown by Rossel and Martínez Arbizu 31,32 . Amongst others, the authors emphasized the importance of sediment sample storage at low temperatures for MALDI-TOF MS applications 32 .…”
Section: Introductionmentioning
confidence: 74%
“…Simultaneous use of individuals for barcoding and analysis in MALDI-TOF MS was shown several times (e.g., Laakmann et al, 2013;Bode et al, 2017;Rossel and Martínez Arbizu, 2018b;Rossel and Martínez Arbizu, 2019) even for small animals such as copepods, implying a possible combination of MALDI-TOF MS and DNA barcoding for biodiversity assessments and monitoring. Voucher specimens can be analyzed by MALDI-TOF MS and sequenced simultaneously to support identifications based on mass spectra by DNA without causing high costs by barcoding of all assessed specimens.…”
Section: Maldi-tof Ms Vs Barcoding Vs Metabarcodingmentioning
confidence: 99%
“…When applying the workflow presented here, attention has to be paid to data origin and quality. For instance, joining data from different studies may cause problems as various factors such as storage and fixation were shown to influence mass spectra quality (Yssouf et al ; Rossel and Martínez Arbizu ). This may affect the species‐specific fingerprint in such a way that single species could be recognized as different species due to mass spectra alteration.…”
Section: Discussionmentioning
confidence: 99%
“…MALDI‐TOF MS data from published mass spectra (Rossel and Martínez Arbizu , c , , b ; Supporting Information Table S1) on harpacticoid copepods were pooled and screened for species with at least 10 specimens. Only specimens reported to be obtained from appropriately stored samples were included and combined into the data set used for this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation